A study on Arbuscular Mycorrhiza diversity in soil and orange roots sampled from Quy Hop, Nghe An - Kim Lien, Nguyen Thi; Thuy, Le Thi; Hiep, Nguyen Viet; Hoang, Nguyen Huy (Academia Journal of Biology, 2013)
Arbuscular Mycorrhyza Fungi (AMF) is the common type of symbiotic between mycorrhiza fungi and plants. They have an important role for the growth of plants, especially in bad environmental conditions. In this paper, we reported results of isolation and identification of AMF species in soil and orange roots sampled in Quy Hop, Nghe An province. The results showed that there were 16 AMF species belonging to six genera namely Acaulospora, Entrophospora, Glomus, Sclerocystis, Glomites and Gigaspora in the collected samples from different soil horizons (0-20 cm, 20-40 cm and 40-60 cm) and roots of three orange cultivars, such as Xa Doai, Van Du and V2. The distribution of AMF on roots of three orange cultivars and three soil horizons were significantly different. The role of AMF was evaluated throught the test to determine the infection of AMF into the young orange trees. Results revealed that the trees which were infected with AMF had roots longer and more number of roots.